Penilaian alur luka untuk menentukan penyebab kematian - Jims Ferdinan; Mistar Ritonga (Fakultas Kedokteran USU, 2012)
The gully injury is often used in explaning the macanisme of the death in establishing etiology of the death. The benefits of injury gully value, besides to determine the cause of death, at also to assist the investigation of the death in establishing the main actor when causing the victim dead, particularly is the incident was executed by many kind of fools and or actors.Keywords: trauma; injury gully; cause of death